2020
DOI: 10.1063/5.0025523
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for electron energization accompanying spontaneous formation of ion acceleration regions in expanding plasmas

Abstract: We report experiments conducted in an expanding argon plasma generated in the inductive mode of a helicon source in the Hot hELIcon eXperiment–Large Experiment on Instabilities and Anisotropies facility. As the neutral gas pressure increases, the supersonic ion acceleration weakens. Increasing neutral pressure also alters the radial profile of electron temperature, density, and plasma potential upstream of the plasma expansion region. Langmuir probe measurements of the electron energy probability function (EEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
5
6
0
Order By: Relevance
“…This is basically consistent with the previous reports [e.g. 35,67,68], indicating a change from edge heating to central heating through the radial electron temperature and electric field profiles as well as power deposition, accompanied by the transition to BC mode. According to this mechanism, the transition from NW to BC mode in a helicon plasma looks like a transition from general helicon waves propagation into the anti-resonance region of TG waves with enhanced volume absorption by helicon waves, although the transition conditions are needed to be clarified.…”
supporting
confidence: 93%
“…This is basically consistent with the previous reports [e.g. 35,67,68], indicating a change from edge heating to central heating through the radial electron temperature and electric field profiles as well as power deposition, accompanied by the transition to BC mode. According to this mechanism, the transition from NW to BC mode in a helicon plasma looks like a transition from general helicon waves propagation into the anti-resonance region of TG waves with enhanced volume absorption by helicon waves, although the transition conditions are needed to be clarified.…”
supporting
confidence: 93%
“…That helped to reduce the collision frequency to maintain high T e at the edge. This phenomenon meant that the central heating by the helicon wave was weakened, while the edge heating in the skin layer was strengthened by stochastic heating [27,33,68] or TG wave [52,69], and this enhancement also meant the change of power dissipation mechanism of the waves with the increase of pressure. It is also shown that the intermediate pressure case exhibits the lowest value rather than the highest pressure in figure 9.…”
Section: ( ) ( )mentioning
confidence: 99%
“…The RF power is mainly absorbed by electrons in the inductively coupled or helicon modes [1]. Note that the neutral energy is negligibly small because the neutral temperature is roughly 300 K, while the measured ion and electron temperatures are 0.1-1 eV [24] and 1-20 eV [25,26], respectively. In addition, the magnetostatic field produced by the solenoid supplies no energy to the plasma.…”
Section: Introductionmentioning
confidence: 97%